Disruption of cellular timekeeping in cancer: links between circadian clocks, metabolism, and tumor progression - Ziaul Karim; Lahanya Guha; Priya Manna; Anjan Gowda BH; Ajay Kumar Gupta; Khalid Rehman Hakeem (Molecular Biology Reports, 2026)

Biochemical and molecular profiling of stress-responsive traits and genes in climate-resilient PGPRs - Deepanjali Gupta; Kiran P. Raverkar; Navneet Pareek; Poonam Gautam; Ajay Veer Singh; Kanchan Karki; Shivanshu Garg; Geetanjali Bhandari (Physiological and Molecular Plant Pathology, 2026)

Hybrid modelling of landslide susceptibility using frequency ratio and maximum entropy models in the MPRRU region of Jammu and Kashmir, India - Ajay Kumar Taloor; Abid Abraham; Amit Jaiswal; Ravi Katiyar; Anil Kumar Gupta; Kanika Sharma; Sunil Kumar Pundir (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Impact of reservoir storage on propagation from meteorological to hydrological drought - Ajay Gupta; Manoj Kumar Jain; Rajendra Prasad Pandey; David M. Hannah (Journal of Hydrology, 2026)

Evolution of intelligent nitrogen management systems: a two-decade global research analysis - Manojit Chowdhury; Suman Dutta; Karishma Kumari; Ayushi Jha; Krishna Mondal; Dhananjay Paswan Das; Pranay Sarkar; Ajay N. Satpute; Subrata Gorain; Vishal Gupta (Computers and Electronics in Agriculture, 2026)

HMG-Former: a hierarchical meta-graph transformer framework for robust multi-class SAR target recognition - Bibek Kumar; Ajay Kumar; Shashi Kant Gupta; Diaa Salama AbdElminaam; Deema Mohammed Alsekait; Mohammed Yahya Albeshri (International Journal of Remote Sensing, 2026)

CRISPR–Cas-based detection of Mycobacterium tuberculosis: current advances and translational bottlenecks - Nour Akkoul; Tarun Kumar; Swaati Sharma; Vipasha Sharma; Vaseem Raja; Tanzil Gaffar Malik; Wan Shafrina Wan Mohd Jaafar; Ajay Kumar Gupta; Khalid Rehman Hakeem (Protoplasma, 2026)

Assessment of bioactive compounds, antioxidant pigments and mineral diversity in leaves of amaranth (Amaranthus spp.) genotypes - Ajay Kumar Sharma; Vidya Sagar; Jyoti Devi; S. V. Dwivedi; Neetu; Vishal Chugh; Ashutosh Rai; Anurag; Nakul Gupta; Rajesh Kumar; N. Rai; T. K. Behera (Genetic Resources and Crop Evolution, 2026)

Current Paradigms in Understanding Neuron Fluctuations, Factors, Regulation, Pathophysiology of Epilepsy: Advancements in Diagnosis, Treatment and Management—An Update - Pooja Sharma; Payal Gupta; Anita Rani Gill; Sunil Kumar; Pawan Kumar; Paavan Singhal; Mahiti Gupta; Raj Singh; Varruchi Sharma; Sharun Khan; Kuldeep Dhama; Ajay Sharma; et al. (Indian Journal of Clinical Biochemistry, 2026)

Characterisation and Detoxification Mechanisms of Agrowaste-Derived Biochars Containing Nanosized Particles for Contaminants of Environmental Concern - Kishore Kumar Krishnani; Veera Mallu Boddu; Ajit Kumar Verma; Govindarajan Venkatesh; Vidya Shree Bharti; Ajay Upadhyay; Moturi Muralidhar; Neeraj Kumar; Gayatri Tripathi; Narinder Kumar Chadha; Sanjay Kumar Gupta (Bulletin of Environmental Contamination and Toxicology, 2026)

Influence of inoculum-to-substrate ratio on process stability and microbial community structure in anaerobic digestion of human faecal matter - Roshita Sharma; Vanshikha Gupta; Vijai Pal; Janardan Sen; Mukesh Kumar Meghvansi; Ajay Kumar Goel (Environmental Science and Pollution Research, 2026)

Deterministic strain engineering through growth-driven stacking in twisted bilayer MoS2 - Pukhraj Prajapat; Vaibhav Kandwal; Jayalekshmi U.J.; Aditya Kushwaha; Neeraj Goel; Ajay Kumar Shukla; Govind Gupta (Chemical Engineering Journal, 2026)

Quantification and characterization of soil organic carbon with different environmental gradients for the high altitude wetlands of Indian Himalaya - Narayan P. Anugraha; D. Ganguly; A. Paneer Selvam; Kakolee Banerjee; M. Harikrishna Prasad; Lakpa Tamang; Sushmita Chettri; Anupriya Soni; Rajesh Joshi; Ajay Kumar Gupta; Prakash Chhetri; Ramachandran Purvaja (Environmental Geochemistry and Health, 2026)

Transgenic and genome editing approaches for starch modification in potato- a review - Sudha Batta; Neha Sharma; Reena Gupta; Brajesh Singh; Ajay Kumar Thakur (Plant Gene, 2026)

Hulless Barley (Hordeum vulgare L.) Variety DWRB 223 - Jogendra Singh; Omvir Singh; R. P. S. Verma; Chuni Lal; Lokendra Kumar; S. K. Bishnoi; Rekha Malik; Dinesh Kumar; OP Gupta; Charan Singh; Poonam Jasrotia; Ravindra Kumar; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Valuing rare earth elements in EV motors: Bottom-up analysis of willingness-to-pay - Ilenia Gaia Romani; Elizabeth A. Moore; Karan Bhuwalka; Ajay Gupta; Richard Roth (Resources, Conservation and Recycling, 2026)

The dietary burden of phosphorus and aluminum in ready-to-eat wheat flour tortillas exceeds that of corn tortillas: Implications for patients with chronic kidney disease - Kate Chander Chiang; Robert A. Yokel; Jason M. Unrine; Kamyar Kalantar-Zadeh; Ajay Gupta (Food and Humanity, 2026)

Cloning and Heterologous Expression of Laccase from Beauveria pseudobassiana PHF4 in E. coli and its Application in the Degradation of Catechol - Divya Sharma; Sudha Batta; Ajay Kumar Thakur; Reena Gupta (Current Microbiology, 2026)

CAR-T cell therapy for pediatric solid tumors: armored CAR-T cells and beyond - Jeremy Wells; Ajay Gupta (Cancer and Metastasis Reviews, 2026)
CAR-T cell therapy, which uses endogenous T cells engineered to target specific cancer antigens, is one of the most promising recent developments in the treatment of hematologic malignancies in both children and adults. CAR-T cells have shown tremendous success in treating B-cell lymphoma, acute lymphoblastic leukemia, and multiple myeloma, and they are currently FDA-approved for the treatment of six hematologic malignancies. Its success in solid tumors has been more modest, which has been attributed to several factors including the hostile tumor microenvironment (TME), poor persistence of CAR-T cells, and difficulty directing CAR-T cells towards solid tumors. Armored CAR-T cells, which modify the TME via secreted cytokines, have shown early success in the treatment of solid pediatric malignancies. We review recent trials of CAR-T cells to treat common pediatric solid malignancies, including Ewing sarcoma, osteosarcoma, neuroblastoma, diffuse intrinsic pontine glioma, rhabdomyosarcoma, Wilms tumor, and retinoblastoma. We focused particularly on armored CAR-T cells where applicable. Armored CAR-T cells have been utilized to target a variety of tumor-associated antigens on pediatric solid tumors with early successes both in vivo and in vitro , and innovative approaches for addressing their limitations are rapidly being developed.

Conservation Agricultural Practices Enhance Food-Water-Economics Nexus and Mitigate Greenhouse Gas Emissions in Maize (Zea mays L.) – Chickpea (Cicer arietinum L.) Cropping System in Central High Lands of India - Chetankumar Prakash Sawant; Krishna Pratap Singh; Ajita Gupta; Bharat Prakash Meena; Ram Kishor Fagodiya; Ajay Singh; Brij Lal Lakaria; Anand Kumar Vishwakarma; Abhijit Khadatkar; Ajit Pralhad Magar; Ved Prakash Chaudhary (International Journal of Plant Production, 2026)

Next-generation strategies for rhamnolipid biosurfactant production: Metabolic optimization and sustainable process development - Yashika Raheja; Satish Kumar Ainala; Tayyab Islam; Pallavi Gupta; Ajay Kumar; Vivek Kumar Gaur; Janmejai kumar Srivastava (Bioresource Technology Reports, 2026)

Detection and molecular characterization of phytoplasma associated with cherry trees in Himachal Pradesh (India) - Aman Chauhan; Anil Handa; Ajay Brakta; Pankaj Kumar; Bhupesh Gupta; Rakesh Daroch; Abhinav Thakur (Crop Protection, 2025)

Assessment of Morphological and Physiochemical Diversity in Longan (Dimocarpus Longan Lour.) Genotypes for Genetic Improvement - Ajay Kumar; A. K. Gupta; Neeharika Kanth; E. S. Marboh; Narayan Lal; Bikash Das (Tropical Plant Biology, 2025)

Exploring extracellular RNA as drivers of chemotherapy resistance in cancer - Yumna Khan; Md Sadique Hussain; Prasanna Srinivasan Ramalingam; Rabab Fatima; Mudasir Maqbool; Sumel Ashique; Najeeb Ullah Khan; Ajay Singh Bisht; Gaurav Gupta (Molecular Biology Reports, 2025)

Comparison of clinical, radiological and outcome parameters in patients with progressive multifocal leukoencephalopathy (PML) with and without HIV infection: a cohort study - Farsana Mustafa; Anuj Ajayababu; Ajay Garg; Megha Brijwal; Divyani Garg; Manish Soneja; Aashish Choudhary; Lalit Dar; Shariq A. Shah; Venugopalan Y Vishnu; Animesh Ray; Neeraj Nischal; et al. (Journal of NeuroVirology, 2025)

Spatial-temporal dynamics of drought in semi-arid river basins using CMIP6 projections - Shashi Bhushan Kumar; Ajay Kumar; Utsav Gupta; Ashok Mishra (Hydrological Sciences Journal, 2025)

Unveiling the chemical composition, bioactive properties, and potential applications of fennel essential oil - Ankita Wal; Divyanshi Gupta; Amin Gasmi; Abida Khan; Astik Manju Ashesh; Ajay Kumar; Dileep Kumar (South African Journal of Botany, 2025)

Synthesis, Characterization and pH-Dependent Surface Charge Modulation of Ethylenediaminetetraacetic Acid Functionalized Cobalt Doped Iron Oxide Nanoparticles for Removal of the Inorganic Impurities - Shweta Patel; Ajay Kumar Gupta (International Journal of Environmental Research, 2025)

Pillared interlayered clays in adsorption and advanced oxidation processes: A sustainable approach for green chemistry - Baneesh Patial; Navdeep; Nitten Kumar; Ajay Bansal; Renu Gupta; Susheel K. Mittal (Applied Clay Science, 2025)

Recent advances and strategies for enhancing perovskite-organic tandem solar cells - Anupam Sharma; Vikas Gupta; Ajay Sharma; Suchinder K. Sharma; Anil Kumar Sharma (Next Research, 2025)

Development of a novel amperometric biosensor utilising Chlorella sp. for determination of organophosphorus pesticides - Baneesh Patial; Manisha Pabbi; Shreya Gupta; Susheel K. Mittal; Ajay Bansal; Renu Gupta (Bioresource Technology Reports, 2025)

Mouse nephron formation is impaired by moderate dose arsenical exposure - Carlos Agustin Isidro Alonso; Jenna Haverfield; Gabriela Regalado; Sihem Sellami; Natascha Gagnon; Ajay Rajaram; Pierre Olivier Fiset; Tomoko Takano; Aimee K. Ryan; Koren K. Mann; Indra R. Gupta (Toxicology and Applied Pharmacology, 2025)

In Vitro and In Silico Evaluation of the Antioxidant and Anticancer Potential of Hamamelitannin from Hamamelis virginiana - Vishnu Adith Janarthanam; Moogambigai Sugumar; Rupesh Gupta; Alaa S. Alhegaili; Ajay Guru; Praveen Kumar Issac (Cell Biochemistry and Biophysics, 2025)

ALR inhibits HBV replication and autophagosome formation by ameliorating HBV-induced ROS production in hepatic cells - Amit Kumar Mishra; Md. Musa Hossain; Teja Naveen Sata; Kishor Pant; Ajay K. Yadav; Amrendra Kumar Sah; Parul Gupta; Md Ismail; Baibaswata Nayak; Shalimar; Senthil Kumar Venugopal (Virus Genes, 2025)

In vitro induction and plant regeneration in potato (Solanum tuberosum L.) cv. Kufri Sangam - Sudha Batta; Ajay Kumar Thakur; Rajender Singh; Sakshi Singh; Pitambri Thakur; Reena Gupta (Vegetos, 2025)

Prediction of hand-arm vibration among tractor operators in different soil tillage operations using artificial neural network-based model - Chander Prakash; Lakhwinder Pal Singh; Ajay Gupta; Amandeep Singh (Computers and Electronics in Agriculture, 2025)

Botany, ethnomedicine, phytochemistry and pharmacology of Amaranthus spp.- a review - Ajay Kumar Sharma; Satya Vart Dwivedi; Jyoti Devi; Nakul Gupta; Nagendra Rai; TK Behera; Vidya Sagar (South African Journal of Botany, 2025)

Estimation of source parameters and scaling relationship of the local earthquakes in the Central Seismic gap NW Himalaya, India - Abhishek Kumar Gupta; Anil Tiwari; Naresh Kumar; Ajay Paul; Kalachand Sain; Dilip Kumar Yadav; Ashish Pal; Debonil Baruah (Journal of Asian Earth Sciences, 2025)

Molecular genetic characterization of porcine reproductive and respiratory syndrome virus outbreak in Assam, India and neighbouring regions - Seema Rani Pegu; Joyshikh Sonowal; Pranab Jyoti Das; Swaraj Rajkhowa; Manjisa Choudhury; Rajib Deb; Gyanendra S. Sanger; Ajay K. Yadav; Nabajyoti Deka; Sunil Kumar; Vivek K. Gupta (Brazilian Journal of Microbiology, 2025)

HIV associated motor neuron disease (MND): A case series with systematic review of literature - Farsana Mustafa; Sapna Mittal; Divyani Garg; Ayush Agarwal; Ajay Garg; Baidnath Kumar Gupta; Manish Soneja; Achal Kumar Srivastava (Journal of NeuroVirology, 2025)

Recent trends in US federal research support for imaging instrumentation grants to departments of radiology - Kelly M. Gillen; Patricia Long; Ajay Gupta (Next Research, 2024)

Scaffold transforming and in-silico design of potential androgen receptor antagonists in prostate cancer therapy - Ajay Kumar Gupta; Piyush Ghode; Sanmati Kumar Jain (In Silico Pharmacology, 2024)

Forecasting revenue from primary and secondary sources of rare earth elements - Ajay Gupta; Eric Williams; Gabrielle Gaustad (Resources, Conservation and Recycling, 2024)

Optimization and kinetic analysis of electrocoagulation-assisted adsorption for treatment of young landfill leachate - Ashmita Kundu; Navinkumar Gupta; Ajay S. Kalamdhad (Journal of Environmental Management, 2024)

Ruthenium doping of NASICON electrolyte augments the performance of solid-state sodium-ion batteries - M. Dinachandra Singh; Deepak Kumar Gorai; Kumar Brajesh; Pragati Singh; Vishal Ranawade; Ajay Vijay Shinde; M. Jareer; Raju Gupta; Ashish Garg; Vishal Agarwal; Kanwar S. Nalwa (Chemical Engineering Journal, 2024)

Assessment of variability and genetic divergence of longan genotypes (Dimocarpus longan Lour.) based on qualitative and quantitative traits - Ajay Kumar; A. K. Gupta; Neeharika Kanth; E. S. Marboh; Sudheer Kumar Yadav (Euphytica, 2024)

Modelling of source parameters of local earthquakes and seismotectonic implications in Siang Valley, NE India - Ashish Pal; Dilip Kumar Yadav; Naresh Kumar; Abhishek Kumar Gupta; Ajay Paul; H C Nainwal (Journal of Earth System Science, 2024)

Prediction of B cell epitopes in envelope protein of dengue virus using immunoinformatics approach - Ajay Kumar; Siddharth Gupta; Hari Om Sharan; Fariya Khan (Journal of Proteins and Proteomics, 2024)

Differential responses of genotype × environment interaction on Agronomic interventions affect the yield and quality of essential oil of interspecific basil hybrid of Ocimum basilicum L. × Ocimum kilimandscharicum - Ajay Kumar; Nilesh Sharma; Ashish Kumar; Dhananjay Kumar; A.C. Jnanesha; Anil Kumar Gupta; C.S. Chanotiya; Deepa Bisht; R.K. Lal (Ecological Genetics and Genomics, 2024)

MYCN immunohistochemistry as surrogate marker for MYCN-amplified spinal ependymomas - Divya Mohan; Aruna Nambirajan; Rafat Malik; Agrima Sharma; Vaishali Suri; Kavneet Kaur; Ramesh Doddamani; Ajay Garg; Subhash Gupta; Supriya Mallick; Mehar Chand Sharma (Human Cell, 2024)

1-D shear wave velocity structure beneath North India using surface wave dispersion study - Abhishek Kumar Gupta; Prantik Mandal; Kalachand Sain; Chinmay Haldar; Ajay Paul (Journal of Earth System Science, 2024)

Evaluation of global precipitation products for meteorological drought assessment with respect to IMD station datasets over India - Ajay Gupta; Manoj Kumar Jain; Rajendra Prasad Pandey; Vivek Gupta; Aniruddha Saha (Atmospheric Research, 2024)

A comprehensive review on spatial and temporal variation of arsenic contamination in Ghaghara basin and its relation to probable incremental life time cancer risk in the local population - Sanjay Dwivedi; Seema Mishra; Vishnu Kumar; Ruchi Agnihotri; Pragya Sharma; Ravi Kumar Tiwari; Apoorv Gupta; Ajay Pratap Singh; Sarvesh Kumar; Geetgovind Sinam (Journal of Trace Elements in Medicine and Biology, 2023)

In-vitro anti-sickling potential of baicalin and naringenin isolated from Oroxylum indicum and Citrus aurantium on human sickle red blood cells - Bashir Ahmad Lone; Nitika Sharma; Dilpreet Kour; Anil Bhushan; Dixhiya Rani; Ajay Kumar; Prashant Kumar Gupta; Prasoon Gupta (Natural Product Research, 2023)

Exploration of the Growing Therapeutic Potentials of Quercetin in Ovarian Cancer Management - Dhruv Sanjay Gupta; Vaishnavi Gadi; Ginpreet Kaur; Madhu Gupta; Ajay Kumar; Hardeep Singh Tuli (Current Pharmacology Reports, 2023)

Hydrothermal synthesis of (m-t)BiVO4/g-C3N4 heterojunction for enhancement in photocatalytic degradation of imidacloprid - Baneesh Patial; Ajay Bansal; Renu Gupta; Susheel K. Mittal (Journal of Environmental Chemical Engineering, 2023)

Advancement in nanotechnology for treatment of rheumatoid arthritis: scope and potential applications - Radha Rani; Neha Raina; Ajay Sharma; Pramod Kumar; Hardeep Singh Tulli; Madhu Gupta (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

One-dimensional regional shear velocity structure from joint inversion of fundamental mode group velocity dispersion measurements of Love and Rayleigh waves: application to the Uttarakhand Himalaya - Abhishek Kumar Gupta; Prantik Mandal; D. Srinagesh; Anil Tiwari; Kalachand Sain; Ajay Paul (Acta Geophysica, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Nanoencapsulation of Docetaxel Induces Concurrent Apoptosis and Necroptosis in Human Oral Cancer Cells (SCC-9) via TNF-α/RIP1/RIP3 Pathway - Parul Gupta; Arpita Singh; Ajay Kumar Verma; Surya Kant; Anuj Kumar Pandey; Anupam Mishra; Puneet Khare; Ved Prakash (Indian Journal of Clinical Biochemistry, 2023)

Exploring global supply and demand of scandium oxide in 2030 - Sinoun Phoung; Eric Williams; Gabrielle Gaustad; Ajay Gupta (Journal of Cleaner Production, 2023)

First report of endophytic Bipolaris axonopicola from untapped Bastar forests, India, producing human lipase and histone deacetylase inhibitors - Soniya Goyal; Poonam Bansal; Paavan Singhal; Raman Kumar; Ajay Gupta; Gurmeen Rakhra; Mahiti Gupta; Abdulrab Ahmed M. Alkhanjaf; Ibrahim Ahmed Shaikh; Ahmad Umar; Mohd. Sayeed Akhtar; Sotirios Baskoutas (South African Journal of Botany, 2023)

Artificial intelligence and machine learning disciplines with the potential to improve the nanotoxicology and nanomedicine fields: a comprehensive review - Ajay Vikram Singh; Mansi Varma; Peter Laux; Sunil Choudhary; Ashok Kumar Datusalia; Neha Gupta; Andreas Luch; Anusha Gandhi; Pranav Kulkarni; Banashree Nath (Archives of Toxicology, 2023)
The use of nanomaterials in medicine depends largely on nanotoxicological evaluation in order to ensure safe application on living organisms. Artificial intelligence (AI) and machine learning (MI) can be used to analyze and interpret large amounts of data in the field of toxicology, such as data from toxicological databases and high-content image-based screening data. Physiologically based pharmacokinetic (PBPK) models and nano-quantitative structure–activity relationship (QSAR) models can be used to predict the behavior and toxic effects of nanomaterials, respectively. PBPK and Nano-QSAR are prominent ML tool for harmful event analysis that is used to understand the mechanisms by which chemical compounds can cause toxic effects, while toxicogenomics is the study of the genetic basis of toxic responses in living organisms. Despite the potential of these methods, there are still many challenges and uncertainties that need to be addressed in the field. In this review, we provide an overview of artificial intelligence (AI) and machine learning (ML) techniques in nanomedicine and nanotoxicology to better understand the potential toxic effects of these materials at the nanoscale.

Valorisation of fruit peel bioactive into green synthesized silver nanoparticles to modify cellulose wrapper for shelf-life extension of packaged bread - Krishna Gopalakrishnan; Mahima Chandel; Vanshita Gupta; Kuljinder Kaur; Ajay Patel; Kamaljit Kaur; Anand Kishore; Pramod K. Prabhakar; Anurag Singh; Jai Shankar Prasad; Vikrant Bodana; Vikas Saxena; et al. (Food Research International, 2023)

Understanding the influence of eccentric pressure tube on the thermal behavior of 37-element based PHWR channel under accident condition - Ketan Ajay; Ravi Kumar; Akhilesh Gupta; Onkar Gokhale; Deb Mukhopadhyay (Annals of Nuclear Energy, 2023)

Epinephrine facilitates the growth of T cell lymphoma by altering cell proliferation, apoptosis, and glucose metabolism - Rajan Kumar Tiwari; Shiv Govind Rawat; Vishal Kumar Gupta; Pradip Kumar Jaiswara; Pratishtha Sonker; Santosh Kumar; Vibhav Gautam; Manoj K. Mishra; Ajay Kumar (Chemico-Biological Interactions, 2023)

Phosphodiesterase 5 inhibitor sildenafil potentiates the antitumor activity of cisplatin by ROS-mediated apoptosis: a role of deregulated glucose metabolism - Shiv Govind Rawat; Rajan Kumar Tiwari; Pradip Kumar Jaiswara; Vishal Kumar Gupta; Pratishtha Sonker; Naveen Kumar Vishvakarma; Santosh Kumar; Chandramani Pathak; Vibhav Gautam; Ajay Kumar (Apoptosis, 2022)

Rapid flash flood calamity in Chamoli, Uttarakhand region during Feb 2021: an analysis based on satellite data - Sunita Verma; Ajay Sharma; Pramod Kumar Yadava; Priyanshu Gupta; Janhavi Singh; Swagata Payra (Natural Hazards, 2022)

Targeting lysophosphatidic acid receptor with Ki16425 impedes T cell lymphoma progression through apoptosis induction, glycolysis inhibition, and activation of antitumor immune response - Vishal Kumar Gupta; Ajay Kumar (Apoptosis, 2022)

Nickel-mediated lead dynamics and their interactive effect on lead partitioning and phytoremediation indices in spinach - Mohan Lal Dotaniya; Jaypal Singh Pipalde; Ramesh Chandra Jain; Rajendiran Selladurai; Subhash Chandra Gupta; Madhav Das Vyas; M Vassanda Coumar; Sonalika Sahoo; Jayanta Kumar Saha; Ajay Kumar (Environmental Monitoring and Assessment, 2022)

Design of an Epitope-Based Peptide Vaccine Against Dengue Virus Isolate from Eastern Uttar Pradesh, India - Siddharth Gupta; Ajay Kumar (International Journal of Peptide Research and Therapeutics, 2022)

Distribution of Fluoride in Plasma, Brain, and Bones and Associated Oxidative Damage After Induced Chronic Fluorosis in Wistar Rats - Priyanka Sharma; Pawan K. Verma; Shilpa Sood; Rajiv Singh; Ajay Gupta; Ankur Rastogi (Biological Trace Element Research, 2022)

Variation in reproductive attributes and diapause behaviour among six populations of Zygogramma bicolorata Pallister - Kamlesh Bali; Rakesh Kumar Gupta; Ahmad Pervez; Mushtaq Ahmad Guroo; Ajay Gupta; Mudasir Gani (International Journal of Tropical Insect Science, 2022)

Numerical and analytical study on uplift capacity of under-reamed piles in sand - Ajay Kumar; Vishwas N. Khatri; Sunil K. Gupta (Marine Georesources & Geotechnology, 2022)

Biocontrol and plant growth promoting potential of Trichoderma yunnanense - Pintu Karmakar; Koyel SenGupta; Panna Das; Swati Gupta Bhattacharya; Ajay Krishna Saha (Vegetos, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Streamflow modeling and contribution of snow and glacier melt runoff in glacierized Upper Indus Basin - Chanchal Gupta; Anil V. Kulkarni; Ajay K Taloor (Environmental Monitoring and Assessment, 2021)

Characterization and performance evaluation of synthesized ZnO nanoflowers, nanorods, and their hybrid nanocomposites with graphene oxide for degradation of Orange G - Renuka Garg; Renu Gupta; Nirmal Singh; Ajay Bansal (Environmental Science and Pollution Research, 2021)

Protein biomarker elucidation for the verification of biological agents in the taxonomic group of Gammaproteobacteria using tandem mass spectrometry - Sasikumar Sabna; Dev Vrat Kamboj; Sakshi Rajoria; Ravi Bhushan Kumar; Prabhakar Babele; Ajay Kumar Goel; Urmil Tuteja; Mahendra Kumar Gupta; Syed Imteyaz Alam (World Journal of Microbiology and Biotechnology, 2021)

Multiple origins of Indian dwarf wheat by mutations targeting the TREE domain of a GSK3-like kinase for drought tolerance, phosphate uptake, and grain quality - Ajay Gupta; Lei Hua; Guifang Lin; Istváan Molnár; Jaroslav Doležel; Sanzhen Liu; Wanlong Li (Theoretical and Applied Genetics, 2021)

MMP-7 derived peptides with MHC class-I binding motifs from canine mammary tumor tissue elicit strong antigen-specific T-cell responses in BALB/c mice - Pavan Kumar Yadav; Shishir Kumar Gupta; Saroj Kumar; Mayukh Ghosh; Brijesh Singh Yadav; Dinesh Kumar; Ajay Kumar; Mohini Saini; Meena Kataria (Molecular and Cellular Biochemistry, 2021)

Identification of Potent Vaccine Candidates Against Campylobacter jejuni Using Immunoinformatics Approach - Nayan Gupta; Ajay Kumar (International Journal of Peptide Research and Therapeutics, 2020)

Comparative analysis of chromosome 2A molecular organization in diploid and hexaploid wheat - Parampreet Kaur; Suruchi Jindal; Bharat Yadav; Inderjit Yadav; Ajay Mahato; Priti Sharma; Satinder Kaur; O. P. Gupta; Jan Vrána; Hana Šimková; Jaroslav Doležel; Bikram Singh Gill; et al. (Molecular Biology Reports, 2020)

Lysophosphatidic acid promotes survival of T lymphoma cells by altering apoptosis and glucose metabolism - Vishal Kumar Gupta; Pradip Kumar Jaiswara; Pratishtha Sonker; Shiv Govind Rawat; Rajan Kumar Tiwari; Ajay Kumar (Apoptosis, 2020)

Exploring Highly Antigenic Protein of Campylobacter jejuni for Designing Epitope Based Vaccine: Immunoinformatics Approach - Nayan Gupta; Fariya Khan; Ajay Kumar (International Journal of Peptide Research and Therapeutics, 2019)

Assessment of the Petroleum Oil Degradation Capacity of Indigenous Bacterial Species Isolated from Petroleum Oil-Contaminated Soil - Alok Dwivedi; Swati Chitranshi; Akanksha Gupta; Ajay Kumar; Jawahar Lal Bhat (International Journal of Environmental Research, 2019)

Effect of carotid image-based phenotypes on cardiovascular risk calculator: AECRS1.0 - Narendra N. Khanna; Ankush D. Jamthikar; Deep Gupta; Tadashi Araki; Matteo Piga; Luca Saba; Carlo Carcassi; Andrew Nicolaides; John R. Laird; Harman S. Suri; Ajay Gupta; Sophie Mavrogeni; et al. (Medical & Biological Engineering & Computing, 2019)

Multienvironmental evaluation of wheat (Triticum aestivum L.) germplasm identifies donors with multiple fungal disease resistance - Satish Kumar; Garima Singroha; S. C. Bhardwaj; Ritu Bala; M. S. Saharan; Vikas Gupta; Anwar Khan; Sunita Mahapatra; M. Sivasamy; Vijay Rana; C. N. Mishra; Om Prakash; et al. (Genetic Resources and Crop Evolution, 2019)

In silico annotation of 458 genes identified from comparative analysis of Full length cDNAs and NextGen Sequence of chromosome 2A of hexaploid wheat - Parampreet Kaur; Inderjit Singh Yadav; Bharat Yadav; Ajay Mahato; O. P. Gupta; J. Dolezel; Nagendra Kumar Singh; J. P. Khurana; Kuldeep Singh (Journal of Plant Biochemistry and Biotechnology, 2019)

Inhibition of Staphylococcus aureus and Pseudomonas aeruginosa Biofilm and Virulence by Active Fraction of Syzygium cumini (L.) Skeels Leaf Extract: In-Vitro and In Silico Studies - Kuldeep Gupta; Salam Pradeep Singh; Ajay Kumar Manhar; Devabrata Saikia; Nima D. Namsa; Bolin Kumar Konwar; Manabendra Mandal (Indian Journal of Microbiology, 2019)

Physicochemical characterization of ferric pyrophosphate citrate - Ajay Gupta; Raymond Pratt; Bhoopesh Mishra (BioMetals, 2018)

Ferric pyrophosphate citrate: interactions with transferrin - Raymond Pratt; Garry J. Handelman; Thomas E. Edwards; Ajay Gupta (BioMetals, 2018)

Biochemical diversity evaluation in chickpea accessions employing mini-core collection - Sameer Suresh Bhagyawant; Ajay Kumar Gautam; Dakshita Tanaji Narvekar; Neha Gupta; Amita Bhadkaria; Nidhi Srivastava; Hari D. Upadhyaya (Physiology and Molecular Biology of Plants, 2018)

Characterization of chickpea (Cicer arietinum L.) lectin for biological activity - Ajay Kumar Gautam; Neha Gupta; Dakshita T. Narvekar; Rajni Bhadkariya; Sameer S. Bhagyawant (Physiology and Molecular Biology of Plants, 2018)

Accurate lumen diameter measurement in curved vessels in carotid ultrasound: an iterative scale-space and spatial transformation approach - P. Krishna Kumar; Tadashi Araki; Jeny Rajan; Luca Saba; Francesco Lavra; Nobutaka Ikeda; Aditya M. Sharma; Shoaib Shafique; Andrew Nicolaides; John R. Laird; Ajay Gupta; Jasjit S. Suri (Medical & Biological Engineering & Computing, 2017)

Site-Specific Fertilizer Nitrogen Management Using Optical Sensor in Irrigated Wheat in the Northwestern India - Bijay-Singh; Varinderpal-Singh; Yadvinder-Singh; H. S. Thind; Ajay Kumar; O. P. Choudhary; R. K. Gupta; Monika Vashistha (Agricultural Research, 2017)

Agroecology as a Climate Change Adaptation Strategy for Smallholders of Tehri-Garhwal in the Indian Himalayan Region - Rajiv Pandey; Roberta Aretano; Ajay K. Gupta; Dhanraj Meena; Bhuvnesh Kumar; Juha M. Alatalo (Small-scale Forestry, 2017)

Empirical assessment of adaptation to climate change impacts of mountain households: development and application of an Adaptation Capability Index - Rajiv Pandey; Nandini Maithani; Roberta Aretano; Giovanni Zurlini; Kelli M. Archie; Ajay K. Gupta; Vishnu Prasad Pandey (Journal of Mountain Science, 2016)

Ferrous iron content of intravenous iron formulations - Ajay Gupta; Raymond D. Pratt; Alvin L. Crumbliss (BioMetals, 2016)

Fertilizer Nitrogen Management in Irrigated Transplanted Rice Using Dynamic Threshold Greenness of Leaves - Bijay-Singh; Varinderpal-Singh; Yadvinder-Singh; Ajay Kumar; Jagmohan-Singh; Monika Vashistha; H. S. Thind; R. K. Gupta (Agricultural Research, 2016)

PPDB: A Tool for Investigation of Plants Physiology Based on Gene Ontology - Ajay Shiv Sharma; Hari Om Gupta; Rajendra Prasad (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Site-specific fertilizer nitrogen management in irrigated transplanted rice (Oryza sativa) using an optical sensor - Bijay-Singh; Varinderpal-Singh; Jaspreet Purba; R. K. Sharma; M. L. Jat; Yadvinder-Singh; H. S. Thind; R. K. Gupta; O. P. Chaudhary; P. Chandna; H. S. Khurana; Ajay Kumar; et al. (Precision Agriculture, 2015)

Synthesis, docking study, and DNA photocleavage activity of some pyrimidinyl hydrazones and 3-(quinolin-3-yl)-5,7-dimethyl-1,2,4-triazolo[4,3-a]pyrimidine derivatives - Ajay Sharma; Vinod Kumar; Rajshree Khare; Girish Kumar Gupta; Vikas Beniwal (Medicinal Chemistry Research, 2015)

Exploitation of microbes for enhancing bacoside content and reduction of Meloidogyne incognita infestation in Bacopa monnieri L - Rupali Gupta; Sudeep Tiwari; Shilpi K. Saikia; Virendra Shukla; Rashmi Singh; S. P. Singh; P. V. Ajay Kumar; Rakesh Pandey (Protoplasma, 2015)

PPDB — A tool for investigation of plants physiology based on gene ontology - Ajay Shiv Sharma; Hari Om Gupta; Rajendra Prasad (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Resource Availability Versus Resource Extraction in Forests: Analysis of Forest Fodder System in Forest Density Classes in Lower Himalayas, India - Rajiv Pandey; Steve Harrison; Ajay Kumar Gupta (Small-scale Forestry, 2014)

Length–Weight Relationships and Condition Factor of Snow Trout, Schizothorax richardsonii (Gray, 1832) From Different Rivers of the Himalayan Region in India - Lalit K. Tyagi; Braj K. Gupta; Ajay Pandey; Amit S. Bisht; Kuldeep K. Lal; Peyush Punia; Rajeev K. Singh; Vindhya Mohindra; Joy K. Jena (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Design of novel anaplastic lymphoma kinase (ALK) inhibitors based on predictive 3D QSAR models using different alignment strategies - Vivek K. Vyas; Ajay Patel; Nirzari Gupta; Manjunath Ghate (Medicinal Chemistry Research, 2014)

Plant proteomics in India and Nepal: current status and challenges ahead - Renu Deswal; Ravi Gupta; Vivek Dogra; Raksha Singh; Jasmeet Kaur Abat; Abhijit Sarkar; Yogesh Mishra; Vandana Rai; Yelam Sreenivasulu; Ramesh Sundar Amalraj; Manish Raorane; Ram Prasad Chaudhary; et al. (Physiology and Molecular Biology of Plants, 2013)

Association of Cadmium and Lead with Antioxidant Status and Incidence of Benign Prostatic Hyperplasia in Patients of Western India - Chirayu Pandya; Sharad Gupta; Prakash Pillai; Ajay Bhandarkar; Arif Khan; Arunodhay Bhan; Akhilesh Prajapati; Sarita Gupta (Biological Trace Element Research, 2013)

Supplementing Fertilizer Nitrogen Application to Irrigated Wheat at Maximum Tillering Stage Using Chlorophyll Meter and Optical Sensor - Bijay-Singh; Varinderpal-Singh; Yadvinder-Singh; H. S. Thind; Ajay-Kumar; Satinderpal-Singh; O. P. Choudhary; R. K. Gupta; Monika Vashistha (Agricultural Research, 2013)

Bortezomib-Induced Congestive Cardiac Failure in a Patient with Multiple Myeloma - Ajay Gupta; Anvita Pandey; Sumit Sethi (Cardiovascular Toxicology, 2012)

Growth and asiaticoside production in multiple shoot cultures of a medicinal herb, Centella asiatica (L.) Urban, under the influence of nutrient manipulations - Archana Prasad; Archana Mathur; Manju Singh; Madan M. Gupta; Girish C. Uniyal; Raj K. Lal; Ajay K. Mathur (Journal of Natural Medicines, 2012)

The first draft of the pigeonpea genome sequence - Nagendra K. Singh; Deepak K. Gupta; Pawan K. Jayaswal; Ajay K. Mahato; Sutapa Dutta; Sangeeta Singh; Shefali Bhutani; Vivek Dogra; Bikram P. Singh; Giriraj Kumawat; Jitendra K. Pal; Awadhesh Pandit; et al. (Journal of Plant Biochemistry and Biotechnology, 2012)

Influence of cellular differentiation and elicitation on intermediate and late steps of terpenoid indole alkaloid biosynthesis in Catharanthus roseus - Ashutosh K. Shukla; Ajit K. Shasany; Ram K. Verma; Madan M. Gupta; Ajay K. Mathur; Suman P. S. Khanuja (Protoplasma, 2010)

Relative performance of neem (Azadirachta indica) coated urea vis-à-vis ordinary urea applied to rice on the basis of soil test or following need based nitrogen management using leaf colour chart - H. S. Thind; Bijay-Singh; R. P. S. Pannu; Yadvinder-Singh; Varinderpal-Singh; R. K. Gupta; Monika Vashistha; Jagmohan Singh; Ajay Kumar (Nutrient Cycling in Agroecosystems, 2010)

QTL analysis for some quantitative traits in bread wheat - Kumar Gupta Pushpendra; Singh Balyan Harindra; Laxminarayan Kulwal Pawan; Kumar Neeraj; Kumar Ajay; Rouf Mir Reyazul; Mohan Amita; Kumar Jitendra (Journal of Zhejiang University-SCIENCE B, 2007)

Gene networks in hexaploid wheat: interacting quantitative trait loci for grain protein content - Pawan Kulwal; Neeraj Kumar; Ajay Kumar; Raj Kumar Gupta; Harindra Singh Balyan; Pushpendra Kumar Gupta (Functional & Integrative Genomics, 2005)

A Kunitz trypsin inhibitor from chickpea (Cicer arietinum L.) that exerts anti-metabolic effect on podborer (Helicoverpa armigera) larvae - Ajay Srinivasan; Ashok P. Giri; Abhay M. Harsulkar; John A. Gatehouse; Vidya S. Gupta (Plant Molecular Biology, 2005)

Production of adventitious shoots and plantlets from the hypocotyl explants of Sesbania rostrata (Bremek & obrem) - Ajay Kumar Jha; Surya Prakash; Neeru Jain; Kanan Nanda; S. C. Gupta (In Vitro Cellular & Developmental Biology - Plant, 2002)

Serum ionised calcium in birth asphyxia - B. K. Jain; Daljit Singh; Harmesh Singh; A. P. S. Narang; Praveen C. Sobti; Ajay Gupta (Indian Journal of Clinical Biochemistry, 2000)